2021
DOI: 10.1021/acsami.1c16302
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Inverse Opal Structure Film for a Rewritable and Double-Sided Photonic Crystal Paper

Abstract: A rewritable photonic crystal (PC) paper as an environmentally friendly and low-resource-consuming material for information storage and spreading has gradually become a research hotspot. In this work, a novel rewritable PC paper with inkless writing and double-sided rewritability properties was developed. A double-sided epoxy resin PC paper exhibiting an inverse opal structure and a bright structural color was fabricated using the sacrificial template method. Carbon black was doped into the material to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Although the studies above have achieved excellent applications of structural color materials utilizing solvent response, the recovery effect of the structural color material swollen multiple times by solvents has not been fully investigated. In our previous study, a double-sided rewritable PC paper was fabricated by epoxy resin, which can be repeated at least 50 times by writing with ethanol, which confirmed that epoxy resin is a suitable material for the preparation of an inverse opal structure. The epoxy-resin inverse opal photonic crystal (EP-IOPC) film is a flexible, easily available, and environmentally friendly material which shows brilliant structure color.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Although the studies above have achieved excellent applications of structural color materials utilizing solvent response, the recovery effect of the structural color material swollen multiple times by solvents has not been fully investigated. In our previous study, a double-sided rewritable PC paper was fabricated by epoxy resin, which can be repeated at least 50 times by writing with ethanol, which confirmed that epoxy resin is a suitable material for the preparation of an inverse opal structure. The epoxy-resin inverse opal photonic crystal (EP-IOPC) film is a flexible, easily available, and environmentally friendly material which shows brilliant structure color.…”
Section: Introductionmentioning
confidence: 61%
“…In addition, the inverse opal structure also led to an obvious increase in the reagent evaporation rate . According to the previous research, the ethanol-infiltrated film structure deformed when ethanol evaporated in air, which is the same as that for acetone; the capillary pressure during the process of the reagents’ evaporation resulted in the morphological deformation of the epoxy resin inverse opal structure. Therefore, the volatilization rate of the reagents can affect the swelling effect of the EP-IOPC film.…”
Section: Resultsmentioning
confidence: 81%
“…Filling pores with liquids of increasing refractive index induces red-shifts of the stop band. This effect has been employed in display and sensing applications, including for the fabrication of rewritable photonic crystal paper . The color of 3DOM materials responds even more strongly to changes in lattice dimensions.…”
Section: Periodic Structurementioning
confidence: 99%
“…On the one hand, CNC films generally show weak visible structure colors under natural light because of strong light scattering. To date, inspired by natural colors with high chroma and saturation enabled by black melanin, 29 black materials, such as carbon black, 30 graphene, 31 polypyrrole, 32 and Fe 3 O 4 , 33 have been introduced into photonic structures for creating vivid structural colors. However, no report has disclosed the possibility of using such a strategy for CNC materials.…”
Section: Introductionmentioning
confidence: 99%